Annual Report on Exchange Arrangements and Exchange Restrictions 2008. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2008)
Published since 1950, this authoritative, annual reference is based upon a unique IMF database that tracks exchange and trade arrangements for all 185 IMF member countries, along with Hong Kong SAR, Aruba, and the Netherlands Antilles. The Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER) draws together information available to the IMF from a number of sources, including during official IMF staff visits to member countries. There is a separate chapter for each of the 187 countries included, and these are presented in a clear, easy-to-read tabular format. A summary table allows for simple cross-country comparisons of key features of their exchange and trade regimes. The report's introduction summarizes recent global trends and developments. It discusses such topical issues as exchange rate arrangements, current or capital transactions, or prudential regulations. The individual country chapters outline exchange measures in place, the structure and setting of exchange rates, arrangements for payments and receipts, procedures for resident and nonresident accounts, mechanisms for import and export payments and receipts, controls on capital transactions, and provisions specific to the financial sector. A separate section in each chapter lists changes made during 2007 and the first half of 2008. The report now provides more detailed information on the operations of foreign exchange markets and exchange rate mechanisms and better describes the regulatory framework for current and capital account transactions. A free demo of a searchable HTML version of the report will be available online.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet